Applying the Kano Model for Analyzing Factors Affecting Patients’ Satisfaction - Ruxandra DINULESCU; Cosmin DOBRIN (Communications of International Proceedings, 2020)
In the present society, medical services and processes are developed based on what patients want and expect, therefore creating an attractive quality, by the healthcare providers, has become fundamental. As a result, healthcare providers must anticipate patients’ needs, as well as, expectations, by contributing with new service characteristics adjusted to patients’ demands, in order to improve their level of satisfaction. The current research aims to explore how the Kano model can be used to identify various patients’ needs towards a continuous improvement of the Romanian private healthcare system. The study’s findings present that there is a variation in the patients’ perceptions related to service quality attributes and so, the service features may be differently organized in Kano’s model. The main objective of the research is to use the Kano model that would increase patients’ satisfaction, by listening to the voice of the patients, as well as, attaining a competitive advantage on the market for the healthcare providers, by presenting high value-added features. Due to its open approach, one of the main advantages of the presented framework is represented by its efficiency to integrate in the private healthcare units, tools for better understanding the voice of the customer, like Kano model.
Keywords: Continuous Improvement; Healthcare System; Quality Attributes; Kano Model.